Strong roots : a memoir of food, family, and Ukraine - Hercules, Olia (Alfred A. Knopf, 2025)
"Strong Roots is the story of a century in Ukraine told through four generations of one extraordinary family. It takes us from years of Russification, to Olia's grandmother's deportation to snowy wastelands under Stalin, to her aunt Zhenia's school protest, to her own parents' flight from Ukraine when their village was occupied in 2022. This is an ode to the land, to ideas of home and belonging, and to family stories and recipes passed down the generations--the tang of sour cherries, the best way to make borsch. It is an account of resilience in the hardest of circumstances. Strong Roots brims with hope and fear. It lays bare the compromises and betrayals of generations struggling and surviving through war, peace, invasion and exile. It is an uplifting reminder of how much the human spirit can endure when born from a land rich with strong roots" --